Acid-resistant UV viscosity-reducing adhesive, UV viscosity-reducing adhesive tape and preparation method of acid-resistant UV viscosity-reducing adhesive tape

By using acid-resistant UV adhesive-reducing adhesives containing carbon-carbon double bonds in UV adhesive tape, an acid-resistant UV adhesive-reducing adhesive with carbon-carbon double bonds, an isocyanate-based crosslinking agent and a photopolymerization initiator, the problems of insufficient viscosity reduction and insufficient acid resistance after UV are solved, and high initial viscosity, low viscosity after UV and good weather resistance are achieved.

CN119570404APending Publication Date: 2025-03-07JIANGSU XINCHENGRUI MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411837239.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing UV adhesive tape does not reduce its viscosity enough after UV irradiation, making it difficult to meet the requirements of acid permeability and erosion resistance during hyaluronic acid etching. At the same time, it exhibits poor weather resistance and adhesion properties during temperature changes and curved surface adhesion.

Method used

An acid-resistant UV adhesive reducing adhesive is adopted, including acrylic polymers containing carbon-carbon double bonds that can be grafted at the side chain or end, an isocyanate crosslinker and a photopolymerization initiator, and a photopolymerization initiator are achieved through specific polymer components and process designs.

Benefits of technology

The high adhesion before UV and easy peeling after UV are achieved, which enhances the resistance to acid erosion during acid etching, and shows good weather resistance and adhesion properties during temperature changes and curved surface adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187044440000101
    Figure BDA0005187044440000101
  • Figure BDA0005187044440000111
    Figure BDA0005187044440000111
Patent Text Reader

Abstract

The invention relates to the technical field of pressure-sensitive adhesives, in particular to a preparation method of a UV (ultraviolet) viscosity-reducing adhesive tape, which comprises the following steps: taking 100g of polymer, adding 10-80g of ethyl acetate, an isocyanate curing agent and a photoinitiator, then uniformly stirring, standing and defoaming to obtain an adhesive, uniformly coating a PET (polyethylene terephthalate) release film with the standing adhesive, putting into a drying oven to bake and dry, then attaching to a PO (polyolefin) base film, and drying to obtain the UV viscosity-reducing adhesive tape. And putting the adhesive tape process product into an aging room, and placing the adhesive tape process product at normal temperature for 7 days to obtain the UV viscosity-reducing adhesive tape of the PO base material. The UV viscosity-reducing adhesive tape disclosed by the invention can realize the performance that a common UV viscosity-reducing adhesive tape cannot be balanced in a severe environment, has the general characteristics of high adhesive force at an initial stage and extremely low adhesive force after UV treatment in the aspect of performance, can resist strong acid corrosion before UV treatment, can be applied to acid etching protection of glass, can be subjected to viscosity-reducing stripping through UV irradiation after an etching process is completed, and is low in adhesive force and high in adhesive force. And automatic operation is easy, and no adhesive residue risk exists.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to an acid-resistant UV viscosity-reducing adhesive, a UV viscosity-reducing tape and a preparation method thereof. Background Art

[0002] The continuous update and development of display technology has driven the continuous innovation of the form of electronic devices such as mobile phones, from plastic pressure touch screens to glass cover touch screens, from flat glass to 2.5D, 3D glass, and then to bendable curved glass, etc. The change in glass form has increased the demand for UV anti-viscosity tape (protective film) and the performance requirements are getting higher and higher. The UV anti-viscosity tape is mainly used for the process protection of mobile phone glass cover cutting and acid etching. Such applications require the UV anti-viscosity tape to have stable viscosity and surface protection requirements in the early stage. After the cutting, acid etching, cutting and other processes are completed, it must be easily removed by UV irradiation without residual glue or degumming damage. This requires that this tape maintains high adhesion before UV irradiation and can quickly reduce the adhesion after UV, and the principle of realizing this adhesion reduction process is that after UV, a large number of double bonds inside the tape undergo cross-linking reactions, and Tg rapidly increases to and loses viscosity. At the same time, in order to meet the requirements of acid penetration and erosion resistance during glass acid etching, the adhesive tape needs to be viscous enough before UV viscosity reduction to prevent the wave impact of the liquid during immersion from causing the tape to fall off from the surface or side of the glass to be etched. It is generally required to be greater than 10N / 25mm, preferably greater than 12N / 25mm, and more preferably greater than 15N / 25mm. However, the conventional UV viscosity reduction adhesive obtained by polymerization has a relatively wide molecular weight distribution in order to obtain high viscosity. The presence of small molecules makes it easy for the acid to penetrate, destroying the appearance of the edge of the etched glass. For example, in patent CN108300352A, in order to meet the acid and alkali resistance characteristics, it is reduced to 0.1N / 25mm after meeting the UV, and the optimal formula can only achieve the initial adhesion of 10N / 25mm. In addition, the initial weather resistance requirements of UV viscosity reduction tape will also be an important trend, because with the increase in the processing procedures and difficulty of mobile phone glass cover plates, it may be placed for a period of time after the UV viscosity reduction film is attached, and even cross-regional transportation between factories may occur, which puts higher requirements on the weather resistance of the tape. For example, the temperature difference between the north and south in autumn and winter can even reach more than 30℃. These huge differences in environment will affect the performance of the tape, and solving the weather resistance problem is also a major issue that needs attention. In addition, with the increasing application of 3D screens and curved screens, the tape as a whole is required to have a certain degree of bendability and adhesion to curved surfaces, an adhesive with a certain degree of anti-warping before UV, and a softer substrate. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a UV anti-viscosity tape, which has excellent adhesion before UV irradiation and can be easily peeled off after UV irradiation without the risk of residual adhesive. When the tape is used as a protective film on the glass surface during acid etching of a mobile phone cover glass, it can protect the surface of the mobile phone cover glass to be etched from being corroded by the acid solution. After the processing is completed, it can be easily and quickly removed by UV irradiation, and is suitable for attaching 3D or curved screens without warping or rebounding.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: an acid-resistant UV viscosity-reducing adhesive, which includes the following components in parts by weight: 100 parts of an acrylic (or methacrylic) polymer containing a carbon-carbon double bond grafted on the side chain or the end and capable of UV light-initiated polymerization, 0.8-1.6 parts of an isocyanate crosslinking agent, and 1.0-3.2 parts of a photopolymerization initiator.

[0005] As a further embodiment of the present invention, the isocyanate crosslinking agent is one or more of aromatic diisocyanate, aliphatic diisocyanate, alicyclic diisocyanate, diisocyanate dimer, and diisocyanate trimer.

[0006] As a further embodiment of the present invention, the isocyanate cross-linking agent is one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and m-tetramethylxylylene diisocyanate.

[0007] As a further embodiment of the present invention, the isocyanate crosslinking agent is a dimer or trimer of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, or m-tetramethylxylylene diisocyanate.

[0008] As a further embodiment of the present invention, the photopolymerization initiator is an acylphosphine oxide-based photopolymerization initiator such as ethyl 2,4,6-trimethylbenzylphenylphosphinate, (2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, 1-hydroxycyclohexylphenyl ketone, α-keto alcohol compounds such as methoxyacetophenone, 2 , 2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone and other acetophenone compounds, benzoin ethyl ether, benzoin isopropyl ether and other benzoin ether compounds, benzyl dimethyl ketal and other ketal compounds, 1-benzophenone-1,1-propanedione-2-(o-ethoxycarbonyl) oxime and other photoactive oxime compounds, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone and other benzophenone compounds or more.

[0009] As a further solution of the present invention, the polymer comprises the following components by weight: 100 parts of (meth)acrylic acid polymer and 5-30 parts of (meth)acrylic acid series oligomer containing C=C double bonds; the polymer A is prepared by free radical thermal polymerization method and amino esterification reaction method to obtain (meth)acrylic acid polymer and (meth)acrylic acid series oligomer containing C=C double bonds; the solid content of the polymer is 33-45%.

[0010] As a further embodiment of the present invention, the polymer comprises the following components by weight: 100 parts of (meth)acrylic polymer and 6-18 parts of (meth)acrylic oligomer containing C=C double bonds.

[0011] As a further embodiment of the present invention, the (meth)acrylic polymer has a hydroxyl group at at least one end or branch chain, and a UV-initiated polymerizable C=C double bond is introduced at at least one end or branch chain, and the radiation-polymerizable C=C double bond is introduced by connecting a monomer containing an isocyanate group and a C=C double bond through an amino esterification reaction with the hydroxyl group on the main chain.

[0012] As a further embodiment of the present invention, the (meth)acrylic acid polymer is 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyhexyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, or (4-hydroxymethylcyclohexyl)methacrylate.

[0013] As a further embodiment of the present invention, the (meth)acrylic acid polymer is 4-hydroxybutyl (meth)acrylate or 2-hydroxyethyl acrylate.

[0014] As a further embodiment of the present invention, the (meth)acrylic acid polymer has a polymerizable active epoxy group capable of cation-initiated polymerization introduced into at least one terminal or branch chain thereof, and the group is introduced by free radical thermal polymerization.

[0015] As a further embodiment of the present invention, the (meth)acrylic polymer is an acrylic monomer.

[0016] As a further embodiment of the present invention, the acrylic monomer is glycidyl (meth)acrylate or 2-ethyl glycidyl (meth)acrylate, epoxy-containing acrylate, allyl glycidyl ether, or glycidyl (meth)acrylate.

[0017] As a further solution of the present invention, the (meth) acrylic acid series oligomer contains at least one UV-initiated polymerizable C=C double bond, has a molecular weight greater than 1000, and contains N element in the molecular structure.

[0018] As a further solution of the present invention, the (meth) acrylic acid-based oligomer contains at least two polymerizable C=C double bonds that can be polymerized by UV initiation, has a molecular weight greater than 3000, and contains N element in the molecular structure.

[0019] As a further embodiment of the present invention, the (meth) acrylic acid oligomer contains at least three UV-initiated polymerizable C=C double bonds, has a molecular weight greater than 5000, and contains N elements in the molecular structure.

[0020] As a further solution of the present invention, the specific steps of the preparation method of the (meth)acrylic acid polymer are as follows:

[0021] Step 1, mixing monomers: mixing and stirring acrylic monomers containing polymerizable C=C in parts by weight to obtain polymerized monomers, wherein the monomer mixture contains monomers containing hydroxyl groups and monomers containing nitrogen elements; the acrylic monomers containing polymerizable C=C are low Tg point soft monomers n-butyl acrylate, and the molecular weight Mw after polymerization is greater than 1 million, more preferably greater than 150W. This macromolecular structure gives the polymer a lower Tg, such as a Tg temperature of less than -20°C, preferably less than -25°C, and more preferably less than -30°C, and has good viscoelasticity and cohesion, while also having good initial viscosity; introducing A Functional groups such as A, 4HBA, HEA, ACMO, etc. can improve the polarity of the molecular chain, which is beneficial to adhesion and viscosity. Moreover, these functional groups can react with the curing agent in the later stage to further improve the cohesion of the adhesive and the acid immersion resistance. By adding monomers containing isocyanate groups and C=C and hydroxyl functional groups through amino esterification reaction, C=C is connected to the main chain, which can be cross-linked by UV free radical initiation. The new groups initiated by grafting in this method have little effect on the molecular weight and structure of the main molecular chain, and can maintain the performance of the polymer main body to the greatest extent; by amino esterification reaction of monomers containing isocyanate functional groups and hydroxyl groups.

[0022] Step 2, adding the polymerizable monomer into a four-necked flask, adding an appropriate amount of solvent, introducing nitrogen under heating in a water bath, and adding a thermal initiator to react for 2-4 hours;

[0023] Step 3, raising the temperature to 78°C within 0.5h to reach reflux, continuing to add thermal initiator and cationic polymerizable acrylic monomer containing epoxy group, and then keeping the temperature for 2-3h, then cooling and stopping nitrogen flow;

[0024] Step 4: Add an acrylate monomer containing an isocyanate group and mix evenly, heat to 40-44°C, then add an organic tin catalyst to react, stop heating after 3-8 hours, add a diluent solvent and stir evenly to obtain a polymer, which introduces an acrylic monomer containing an active epoxy group. Through the initiation of such monomers, efficient cationic initiation crosslinking can be carried out during subsequent UV curing, further reducing the adhesion after UV.

[0025] As a further embodiment of the present invention, the (meth) acrylic monomer containing an isocyanate group is 2-methacryloyloxyethyl isocyanate, 1,1-(bisacryloyloxymethyl)ethyl isocyanate, 2-acryloyloxyethyl isocyanate, or 2-(2-methacryloyloxyethyloxy)ethyl isocyanate.

[0026] As a further embodiment of the present invention, a thermal polymerization method using an azo polymerization initiator as a reaction initiator is adopted.

[0027] As a further embodiment of the present invention, the azo polymerization initiator is 2,2'-azobisisobutyronitrile or 2,2'-azobis-2-methylbutyronitrile or 2,2'-azobis(2-methylpropionic acid)dimethyl ester or 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile.

[0028] As a further solution of the present invention, the time for introducing nitrogen in step 2 is 1 hour, the nitrogen rate is 500 ml / min, and the water bath temperature is 63-67°C.

[0029] As a further solution of the present invention, the solid content of polymer B in step 4 is 20-32%.

[0030] A method for preparing a UV anti-viscosity tape includes an acid-resistant UV anti-viscosity adhesive, and the specific steps are as follows:

[0031] Step 1: Take 100g of the polymer, add 10-80g of ethyl acetate, 0.8-1.6g of isocyanate curing agent, and 1.0-3.2g of photoinitiator, then stir evenly and let stand to degas to obtain an adhesive;

[0032] Step 2, evenly coating the standing adhesive on the PET release film, baking and drying it in an oven, and then attaching it to the PO base film to obtain a tape process product;

[0033] Step 3: Place the tape in-process product in an aging room and place it at room temperature for 7 days to obtain a UV-reduced adhesive tape with a PO substrate.

[0034] As a further embodiment of the present invention, the photoinitiator is a mixture of a free radical photoinitiator and a cationic photoinitiator; the free radical photoinitiator is 184 or TPO or 1173, and the cationic photoinitiator is ITX or 1176 or I-250.

[0035] As a further solution of the present invention, the UV anti-viscosity tape is used as a tape in the process of protecting the glass surface during acid etching or cutting of the glass cover plate of the electronic device.

[0036] Since the present invention adopts the above technical solution, the present invention has the following advantages and positive effects:

[0037] 1. The main adhesive resin polymer is matched with two components, (meth) acrylic polymer and (meth) acrylic oligomer, to achieve the required performance balance, which can achieve a wider distribution of different molecular chains and the complementarity of multi-structure performance, and has a greater possibility of adjusting the initial high viscosity and the low viscosity after UV exposure viscosity reduction;

[0038] 2. Through the combination of multiple reaction modes and special polymerization sequence in (meth) acrylic polymer, the main molecular chain obtains two reactive groups that can be initiated by UV light irradiation, namely, free radical polymerization containing C=C double bonds and cationic polymerization containing active epoxy groups, so that the main resin reacts more fully and faster after exposure and viscosity reduction, and the required exposure energy is lower, which improves the exposure efficiency, increases the degree of reaction, and has lower viscosity after viscosity reduction, making it easier to quickly peel off the automated production line. At the same time, the initiation of multiple polar groups can "lock" more firmly when attached to the glass, and has better acid corrosion resistance;

[0039] 3. By adding (meth) acrylic acid polymers, the molecular weight can be further adjusted and the initial adhesion can be improved. The introduction of multi-functional groups also makes the UV curing cross-linking degree and efficiency higher, and the post-UV adhesion and 90° peeling force lower. DETAILED DESCRIPTION

[0040] Polymerization method of (meth)acrylic acid polymer B of the present invention

[0041] Step 1, mixing monomers: 67-83 parts of n-butyl acrylate, 4-12 parts of 4-hydroxybutyl acrylate, 1-3 parts of methyl methacrylate, 2-9 parts of isobornyl acrylate, 1-7 parts of acrylic acid, 2-5 parts of N,N-dimethyl(meth)acrylamide, and 0.5-4 parts of acryloylmorpholine are mixed and stirred uniformly by weight to obtain a polymerized monomer;

[0042] Step 2: Add the polymerization monomer into a four-necked flask, add 160-240 parts of solvent, introduce nitrogen under water bath heating conditions, then add 0.1-0.3% azobisisobutyronitrile to start the reaction, and the reaction lasts for 3-5 hours; the initiator azobisisobutyronitrile can be added all at once or in steps;

[0043] Step 3: Raise the temperature to 77-84°C for 0.2-0.6h to reach reflux, continue to add 0.1-0.3% azobisisobutyronitrile and 2-7 parts of glycidyl methacrylate, keep warm for 1-4h, then cool and stop nitrogen flow;

[0044] Step 4, add 4-12 parts of isocyanoethyl methacrylate, mix evenly, heat to 39-43°C, then add 0.3-0.8% of dibutyltin dilaurate, start the reaction, last for 3-6 hours, stop heating, add 80-160 parts of diluent solvent and stir evenly, (meth)acrylic acid polymer B;

[0045] The nitrogen was introduced for 1 hour at a rate of 500 ml / min and at a temperature of 63-67°C.

[0046] Preparation method of UV anti-viscosity tape of the present invention

[0047] Step 1: Take 100g of polymer A adhesive, add 10-80g of ethyl acetate, 0.8-1.5g of isocyanate curing agent, and 0.8-3.0g of photoinitiator, then stir evenly and let stand to degas;

[0048] Step 2: Evenly coat the standing adhesive on a 50 μm PET release film, bake it in a 100-120° C. oven for 2-5 minutes, and the adhesive layer thickness is 10 μm. Then, attach it to a 100 μm PO base film to obtain a tape product.

[0049] Step 3, placing the tape in process in an aging room and leaving it at room temperature for 7 days to obtain a finished PO-based UV-reducing tape;

[0050] The photoinitiator is obtained by mixing 0.4-1.8g of a first photoinitiator and 0.2-1.2g of a second photoinitiator; the first photoinitiator 1 is 184 or TPO or 1173; the second photoinitiator is a cationic initiator, and the cationic initiator is ITX or 1176 or I-250.

[0051] DY-12, dibutyltin dilaurate; CN8007NS is a commercially available polymer from Sartomer; isocyanate curing agent L-75 was purchased from Anzu Chemical; the remaining monomers or additives listed can be obtained through commercially available products.

[0052] In the peeling test in the table, ○ represents no residual glue, △ represents star-shaped residual glue, and × represents local flaky or worse residual glue.

[0053] The adhesion test method is as follows: the SUS / Glass board is tested with a sample width of 25 mm, and the board is attached in an environment of 23°C × 50% RH, and a 2Kg roller is rolled back and forth 3 times. After leaving the board for 20 minutes, a peeling test is performed at 300 mm / min and 180°C, and the test results are recorded.

[0054] The holding force test method is as follows: the SUS plate is tested with a pasting area of ​​25mm×25mm, a 2Kg roller is rolled back and forth 10 times, placed in an 85°C oven for 20 minutes, and then a 1Kg weight is loaded at 180° for 24 hours, and the moving distance is recorded in mm.

[0055] The test method for initial adhesion after UV is: cut the sample into 1cm wide squares, fix the back of the substrate (non-adhesive surface) to a 1cm wide rectangular steel column with high-strength structural adhesive, and then attach the adhesive surface to a 25mm wide square glass sheet. After UV exposure, pull it away from the steel column at 90° and record the test force. It is generally believed that <50gf / 25mm is easy to peel.

[0056] Acid resistance test: Cut the sample into 77mm*52mm wide strips, prepare 2 strips, and attach them to both sides of the glass plate with a thickness of 2mm and a length of 75mm*50mm. After the bonding is completed, vacuum degassing is carried out at 0.3Mpa for 20 minutes, and then the attached glass pieces are placed in the prepared hydrofluoric acid with a concentration of 15%, soaked for 90 minutes, and the degree of erosion of the glass edge is observed under a microscope.

[0057] Peeling test: Glass board was tested with a sample width of 25mm. It was attached in an environment of 23℃×50%RH and rolled back and forth 3 times with a 2Kg roller. After leaving it for 60 minutes, it was exposed to UV for viscosity reduction. Then, a peeling test was performed on a high-speed peeling machine at 10m / min and 180℃ to observe the residual glue on the glass surface.

[0058] Example

[0059] The monomer content of the adhesive resin prepared in Examples 1-8, the content of each component in the modified adhesive coating and the performance test are shown in Table 1

[0060]

[0061] Table 1

[0062] Comparative Example

[0063] The monomer content of the adhesive resin prepared in Comparative Examples 1-8, the content of each component in the modified adhesive coating and the performance test are shown in Table 2

[0064]

[0065] Table 2

[0066] As can be seen from Table 1 and Table 2, the acid-resistant UV-reducing adhesive provided by the present invention adopts a combination of various polymerization methods such as solvent-based free radical polymerization, and can achieve balanced performance through reasonable formula design and special polymerization process route design. The present invention provides a tape that uses the adhesive provided by the present invention as a coating and uses a PO film with excellent flexibility as a substrate. In terms of performance, it not only has the basic requirements of pressure-sensitive adhesives such as high adhesion and high cohesion before UV, but also has good acid resistance before UV and easy peeling after UV. The initial adhesion of the tape is above 16N / 25mm, and it can be maintained for more than 24 hours without falling at 85°C and 1kg load. It can withstand 15% hydrofluoric acid without penetration and degumming, and has excellent peeling properties after UV.

[0067] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. An acid-resistant UV viscosity-reducing adhesive, characterized in that: The adhesive comprises the following components by weight: 100 parts of an acrylic (or methacrylic) polymer (A) having a carbon-carbon double bond grafted on the side chain or the end and capable of UV light-induced polymerization, 0.8-1.6 parts of an isocyanate crosslinking agent, and 1.0-3.2 parts of a photopolymerization initiator.

2. The acid-resistant UV viscosity-reducing adhesive according to claim 1, characterized in that: The polymer (A) comprises the following components by weight: 100 parts of a (meth)acrylic acid polymer (B) and 5-30 parts of a (meth)acrylic acid oligomer (C) containing a C=C double bond; the polymer A is prepared by a free radical thermal polymerization method and an amino esterification reaction method to obtain the (meth)acrylic acid polymer (B) and the (meth)acrylic acid oligomer (C) containing a C=C double bond; the solid content of the polymer (A) is 33-45%.

3. The acid-resistant UV viscosity-reducing adhesive according to claim 2, characterized in that: The (meth)acrylic polymer (B) has a hydroxyl group at at least one terminal or branch chain, and a polymerizable C=C double bond that can be polymerized by UV initiation is introduced at at least one terminal or branch chain.

4. The acid-resistant UV viscosity-reducing adhesive according to claim 2, characterized in that: The (meth)acrylic polymer (B) has a polymerizable active epoxy group capable of cation-initiated polymerization introduced into at least one terminal or branch chain.

5. The acid-resistant UV viscosity-reducing adhesive according to claim 2, characterized in that: The (meth) acrylic acid-based oligomer (C) contains at least one polymerizable C=C double bond that can be polymerized by UV initiation, has a molecular weight greater than 1000, and contains N element in its molecular structure.

6. The acid-resistant UV viscosity-reducing adhesive according to claim 2, characterized in that: The specific steps of the preparation method of the (meth)acrylic acid polymer (B) are as follows: Step 1, mixing monomers: mixing and stirring the polymerizable C=C acrylic monomers in parts by weight to obtain polymerizable monomers, wherein the monomer mixture contains a hydroxyl-containing monomer and a nitrogen-containing monomer; Step 2, adding the polymerizable monomer into a four-necked flask, adding an appropriate amount of solvent, introducing nitrogen under heating in a water bath, and adding a thermal initiator to react for 2-4 hours; Step 3, raising the temperature to 78°C within 0.5h to reach reflux, continuing to add thermal initiator and cationic polymerizable acrylic monomer containing epoxy group, and then keeping the temperature for 2-3h, then cooling and stopping nitrogen flow; Step 4, add an acrylate monomer containing an isocyanate group and mix evenly, heat to 40-44° C., then add an organic tin catalyst to react, stop heating after 3-8 hours, add a diluent solvent and stir evenly to obtain a polymer (B).

7. The acid-resistant UV viscosity-reducing adhesive according to claim 6, characterized in that: In the step 2, the nitrogen is introduced for 1 hour at a nitrogen rate of 500 ml / min and the water bath temperature is 63-67°C.

8. The acid-resistant UV viscosity-reducing adhesive according to claim 6, characterized in that: The solid content of the polymer (B) in step 4 is 20-32%.

9. A method for preparing a UV anti-viscosity tape, characterized in that: The method comprises the acid-resistant UV viscosity-reducing adhesive according to any one of claims 1 to 8, wherein the specific steps are as follows: Step 1: Take 100 g of polymer (A), add 10-80 g of ethyl acetate, 0.8-1.6 g of isocyanate curing agent, and 1.0-3.2 g of photoinitiator, then stir evenly and let stand to degas to obtain an adhesive; Step 2, evenly coating the standing adhesive on the PET release film, baking and drying it in an oven, and then attaching it to the PO base film to obtain a tape process product; Step 3: Place the tape in-process product in an aging room and place it at room temperature for 7 days to obtain a UV-reduced adhesive tape with a PO substrate.

10. The method for preparing a UV adhesive tape according to claim 9, characterized in that: The photoinitiator is a mixture of a free radical photoinitiator and a cationic photoinitiator; the free radical photoinitiator is 184 or TPO or 1173, and the cationic photoinitiator is ITX or 1176 or I-250.

Citation Information

Patent Citations

  • Acid and alkali resistant UV visbreaking composition, UV visbreaking film and preparation method thereof

    CN108300352A

Cited By

  • Acid and alkali resistant UV visbreaking adhesive, visbreaking adhesive film and visbreaking adhesive tape

    CN121427450A

  • Hybrid adhesive composition for laser processing, method for manufacturing the same, and adhesive protective tape using the same

    JP2026146746A